6x+2=4x+44

Simple and best practice solution for 6x+2=4x+44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2=4x+44 equation:


Simplifying
6x + 2 = 4x + 44

Reorder the terms:
2 + 6x = 4x + 44

Reorder the terms:
2 + 6x = 44 + 4x

Solving
2 + 6x = 44 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2 + 6x + -4x = 44 + 4x + -4x

Combine like terms: 6x + -4x = 2x
2 + 2x = 44 + 4x + -4x

Combine like terms: 4x + -4x = 0
2 + 2x = 44 + 0
2 + 2x = 44

Add '-2' to each side of the equation.
2 + -2 + 2x = 44 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = 44 + -2
2x = 44 + -2

Combine like terms: 44 + -2 = 42
2x = 42

Divide each side by '2'.
x = 21

Simplifying
x = 21

See similar equations:

| c=(5/9)-45 | | 9x-(6x-5)=29 | | 0.083*(cos(3.46*t))+0.029*(sin(3.46*t))=0 | | P(x)=2x^3-6x^2+4x-12 | | 10r+70+49-r^2=169 | | w+(2)(-2)+3(4)=2 | | 0.083*cos(3.46*t)+0.029*sin(3.46*t)=0 | | 4x+6=-2x+x-19 | | 6x+10*5x+20= | | (2x-24)+(((2x-24)*2)-24)+((((2x-24)*2)-24)*2)-24=0 | | P(x)=2x^4-2x^3+8x^2-8x | | 6x-5-3x=14-5x-3 | | 61.8r+440+6.18(49-r^2)=338*3.14 | | 3(2x+3)=18 | | 45-74d-90-4d+4+4d= | | 5(x-24)=20 | | n^2-165=0 | | 2y^2-3Y^3-6y^2+7y^3= | | 4x+1-3x=5 | | x^2+4=169 | | 2(1+x)=8 | | -5/9=-2v+1/3 | | (x+25)+125=10 | | x-.70=154 | | r^2-10r-50=0 | | 9x-21+7x-3=180 | | (x+5)(x+4)=0 | | 3x+6=y | | 3x+6=2+x | | 2p+3=5p-7 | | 7x+3=180 | | 10x+-19=19+-8x |

Equations solver categories